2022
DOI: 10.1111/jace.18826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructures on dielectric breakdown strength of sintered reaction‐bonded silicon nitride ceramics

Abstract: Silicon nitride (Si3N4) was prepared from silicon by a sintered reaction‐bonded silicon nitride method using yttria and magnesia as sintering additives. Post‐sintering (PS) of nitrided compacts was carried out at 1850°C under a nitrogen pressure of 1 MPa. Effect of PS time on microstructure and dielectric breakdown strength (DBS) of the prepared Si3N4 ceramics was evaluated. The DBS was measured using specimens with four different thicknesses (0.30, 0.20, 0.10, and 0.05 mm) in order to examine the thickness de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The parameters on which the properties of Si3N4 depend are the sintering temperature and holding time in addition to the size, ratio, and type of sintering additives [38]. When the sintering temperature and holding time are increased, it has the effect of promoting the growth of b-Si3N4 grains.…”
Section: Ieee Transactions On Dielectrics and Electrical Insulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters on which the properties of Si3N4 depend are the sintering temperature and holding time in addition to the size, ratio, and type of sintering additives [38]. When the sintering temperature and holding time are increased, it has the effect of promoting the growth of b-Si3N4 grains.…”
Section: Ieee Transactions On Dielectrics and Electrical Insulationmentioning
confidence: 99%
“…Additionally, the crystal lattice's oxygen content is continuously lowered by the dissolving-precipitate process, which in turn enhances the thermal and dielectric properties. However, for thinner thickness, this leads to lower breakdown strength decreasing from 99.5 kV/mm to 9.8 kV/mm only when sintering period was increased from 6 hours to 48 hours [38]. Additionally, impurities interfere with the additive/substrate interface leading to the formation of cracks, and defects and drastically reduce the properties of Si3N4.…”
Section: Ieee Transactions On Dielectrics and Electrical Insulationmentioning
confidence: 99%
“…Matsunaga et al 5) reported that large grains function as defects for dielectric breakdown. Our previous work 6) showed that grains with the lengths larger than the substrate thickness can act as fatal defects. Despite these defects, Si 3 N 4 substrates have relatively high DBS; 4), 5) for example, our another study on DBS of Si 3 N 4 7) showed a very high value of 1.5 kV even with a substrate whose thickness was as small as 15 ¯m.…”
Section: Introductionmentioning
confidence: 99%
“…For example, because of their excellent mechanical properties and high thermal conductivity, Si 3 N 4 ceramics are nowadays applied to heat‐dissipating substrates of power devices 9,10 . However, their thickness is required to be less than a few 100 µm for improving their heat dissipation ability, whereas the Si 3 N 4 grain size ranges to several 10 µm 11 . In such cases, the single‐crystal grains themselves play a significant role in determining the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, their thickness is required to be less than a few 100 µm for improving their heat dissipation ability, whereas the Si 3 N 4 grain size ranges to several 10 µm. 11 In such cases, the single-crystal grains themselves play a significant role in determining the material properties. Therefore, it is critically important to correctly evaluate and understand the mechanical behaviors of Si 3 N 4 single crystals for ensuring their structural reliability.…”
Section: Introductionmentioning
confidence: 99%